Remarkable geographical variations between India and Europe in carriage of the staphylococcal surface protein-encoding sasX/sesI and in the population structure of methicillin-resistant Staphylococcus aureus belonging to clonal complex 8. (May 2019) - De Backer, S.; Xavier, B.B.; Vanjari, L.; Coppens, J.; Lammens, C.; Vemu, L.; Carevic, B.; Hryniewicz, W.; Jorens, P.; Kumar-Singh, S.; Lee, A.; Harbarth, S.; et al.
Abstract: Objectives: sasX is a colonization-virulence factor that potentially underlies the success of methicillin-resistant Staphylococcus aureus (MRSA) sequence type (ST) 239 in Asia. We aimed to study the spread of sasX and the population structure of MRSA in two geographically distinct regions, Europe and India. Methods: MRSA ( n  = 128) from screening and clinical samples from tertiary care patients in 12 European countries ( n  = 119), and from India ( n  = 9) were multilocus-sequence-typed and screened for sasX and its carrier φSPβ-like prophage by PCR. Whole genome sequencing was performed on sasX -harbouring strains from India ( n  = 5) and Europe ( n  = 2) and on a selection non-harbouring sasX ( n  = 36) (2 × 150 bp, Miseq, Illumina). Reads were mapped to the ST239 reference strain, TW20. Results: sasX and sesI, a sasX homologue native to Staphylococcus epidermidis, were detected in five of the nine Indian MRSA belonging to ST239 and to other sequence types of CC8. In contrast, sasX was restricted to two ST239 strains in Europe. The intact sasX and sesI carrier φSPβ-like prophages were ∼80 kb and ∼118 kb, and integrated in the yeeE gene. We identified 'novel' ST239 clades in India and Serbia that showed significant differences in base substitution frequencies (0.130 and 0.007, respectively, Tamura–Nei model) (p <0.05). Conclusions: Our data highlight dissemination of sasX to non-ST239 sequence types of CC8. Detection of the S. epidermidis -associated sesI in MRSA provided unquestionable evidence of transfer between the two species. Stark differences in evolutionary rates between the novel Indian and Serbian ST239 clades identified here might be due to inherent clade characteristics or influenced by other environmental differences such as antibiotic use.